Foreign policy : thinking outside the box - Etzioni, Amitai (Abingdog Routledge, 2016)
This collection of essays by renowned scholar Amitai Etzioni aims to provoke reconsiderations of basic assumptions of foreign policy by students, academics and practitioners. With chapters focusing on the Middle East, China and the EU, as well as articles with a more global focus, the book offers thought-provoking and insightful perspectives on international foreign policy which challenge existing academic debate in the field. It will be of great interest to students, scholars and practitioners of foreign policy and international relations.
Include Index
Keywords: World politics -- International relations